A Review on Power Electronics and Drives in Electric Propulsion System. Issue 1 (September 2020) - Shivam, Saurabh; Singh, Rohan; Raja Singh, R.; Sitharthan, R
Abstract: This era is the part of the fast-growing world and it is thriving more in the field of advancement of technology. Power electronics and drives are one of the major fields that is getting updated every day. Due to increased power generation capacity, improved power qualities, increased automation, and improved capabilities, the electric propulsion has replaced mechanical propulsion. Similarly, the variable speed motors have replaced transverse motor starters to save energy and reduce load instability. With the detailed structure and working of the marine electric propulsion system, this paper focus on reviewing about the various power electronic devices and converter configurations that are used in marine applications, specifically in the propulsion system. Moreover, the detailed assessment of different motor and drive schemes employed in propulsion system is carried out. Further, the review will shift its centre towards controlling drives, which includes various control strategies and control techniques.